The Existence of Undergrowth at Forest Garden Stands in Grand Forest Park, Lampung Province - Indriyanto, Indriyanto; Indriyanto, Nurani Hardikananda (Jurnal Biodjati, 2023)
The existence of undergrowth has an important role as an ecosystem both from an ecological and economic perspective. However, the composition and diversity of undergrowth in an area depends on the land use system. This research aimed to know the species composition and diversity of undergrowth at forest garden stands. Data collection was carried out with a vegetation survey using nested rectangular plots with a sampling intensity of 1%. The data collected included undergrowth species, the number of individuals for each species, and tree species as components of forest garden stands. Data were analyzed by calculating density, frequency, important value index, and Shannon diversity index. The results showed that the undergrowth that exists under forest garden stands were 38 species dominated by 12 species, namely Acalypha australis, Asystasia gangetica, Clidemia hirta, Starchytarpeta jamaicensis, Mikania micrantha, Peperomia pellucidia, Setaria barbata, Andropogon aciculatus, Alpinia galanga, Diplazium esculentum, Paederia foetida, and Crassocephalum crepidioides. The forest garden stands were composed of 43 tree species dominated by 4 tree species, namely Durio zibethinus, Aleurites moluccana, Myristica fragrans, and Gnetum gnemon. The level of undergrowth diversity was in the medium category with an H value of 1.540, indicating the diverse of undergrowth species.